2012
DOI: 10.1091/mbc.e11-12-1056
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin activation of Aurora-A kinase (AURKA) is required during ciliary disassembly and in mitosis

Abstract: This study demonstrates for the first time that binding of calcium-activated calmodulin to a minimal interaction site within the disordered N-terminal domain is required for the essential Aurora-A activity in mitosis and in regulation of ciliary disassembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 137 publications
(155 citation statements)
references
References 49 publications
5
150
0
Order By: Relevance
“…Nedd9 binding and activation of Aurora-A is required for ciliary resorption (12,31), and we have observed that Aurora-A expression is elevated in the cystic tissue of patients with ADPKD (20). These results suggested the hypothesis that defects in Aurora-A activation at cilia might underlie the observed trafficking and morphological defects.…”
Section: Nedd9mentioning
confidence: 59%
“…Nedd9 binding and activation of Aurora-A is required for ciliary resorption (12,31), and we have observed that Aurora-A expression is elevated in the cystic tissue of patients with ADPKD (20). These results suggested the hypothesis that defects in Aurora-A activation at cilia might underlie the observed trafficking and morphological defects.…”
Section: Nedd9mentioning
confidence: 59%
“…Increases in cellular levels of phospho-AURKA are associated with an increase in cilia disassembly (Pugacheva et al, 2007;Plotnikova et al, 2012) and similar defects are observed in Inpp5e 2/2 cells (Bielas et al, 2009). To determine whether there was a shared functional basis to these phenotypes, we serum starved fibroblasts from wild-type and Inpp5e 2/2 mice and profiled cilia disassembly upon the addition of serum in the presence or absence of an AURKA inhibitor (C1368) or vehicle control (DMSO).…”
Section: Functional Dissection Of the Role Of The Aurka-inpp5e Interamentioning
confidence: 79%
“…Plasmids, cell culture and inhibitors AURKA and catalytically inactive AURKA (K162R) were expressed from pcDNA3.1-mRFP vector (Plotnikova et al, 2012), murine wild-type INPP5E, INPP5E D480N and INPP4B were expressed from pcDNA3.1-HA, and FLAG-INPP5E was expressed from pcDNA3.1-Flag. V5-tagged human wild-type INPP5E and INPP5E containing Joubert syndrome (JBTS) missense mutations were cloned into pLenti6.2/V5-DEST (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations